Edwards, Sebastian. The Chile Project: The Story of the Chicago Boys and the Downfall of Neoliberalism - Soto, Raimundo (Journal of Economic Literature, 2026)
Raimundo Soto of Pontificia Universidad Catolica de Chile reviews “The Chile Project: The Story of the Chicago Boys and the Downfall of Neoliberalism” by Sebastian Edwards. The Econlit abstract of this book begins: “Explores the rise and fall of the neoliberal model installed by US-influenced economists in Chile during the dictatorship of Augusto Pinochet, highlighting the persistent inequality and struggle for income and wealth distribution underlying the Chilean model's success.”